SLC6A8 Knockdown Suppresses the Invasion and Migration of Human Hepatocellular Carcinoma Huh-7 and Hep3B Cells - Yuan, Lu (Technol Cancer Res Treat, 2020)
Liver cancer is considered the sixth most commonly diagnosed cancer and the fourth leading cause of cancer-related deaths worldwide. Currently, there is no specific and effective therapy for hepatocellular carcinoma. Therefore, developing novel diagnostic and therapeutic strategies against hepatocellular carcinoma is of paramount importance. Solute carrier family 6 member 8 (SLC6A8) encodes the solute carrier family 6-8 to transport creatine into cells in a Na(+) and Cl(-)- dependent manner. SLC6A8 deficiency is characterized by intellectual disabilities, loss of speech, and behavioral abnormalities. Of concern, the association of SLC6A8 with hepatocellular carcinoma remains elusive. In this study, we revealed that SLC6A8 knockdown significantly induced apoptosis and suppressed the migration and invasion of Hep3B and Huh-7 cells. These findings depicted the vital role of SLC6A8 in the initiation and progression of human hepatocellular carcinoma.